Pathways to power : the domestic politics of South Asia - Guneratne, Arjun (ed.) (New Delhi)
Pathways to Power introduces the domestic politics of South Asia in broad comparative perspective, revealing the interplay between politics, cultural values, human security and historical luck. While these are important correlations everywhere, nowhere are they more compelling than in South Asia where such dynamic interchanges loom large on a daily basis. Identity politics, not just of religion but also of caste, ethnicity, regionalism and social class, infuses all aspects of social and political life in the sub-continent. Recognizing this complex interplay, this volume moves beyond conventional views of South Asian politics as it explicitly weaves the connections between history, culture and social values into its examination of political life. The volume covers the five major South Asian states and includes a comprehensive grounding of the politics of modern South Asia in their shared colonial history, tracing how institutions inherited from British rule - parliament, constitutions, judicial systems, the civil service - have diverged in the context of the different social and cultural forces that shape politics in the successor states of Britain's South Asian empire. The book examines the many factors that bring together the disparate countries of the region into important engagements with one another, forming an uneasy regional entity. South Asian readers will find useful ways of comparing the five major South Asian countries through consistent themes that enable a richer understanding of domestic politics throughout the region. Although the book is intended primarily for students of South Asian politics, it also serves as an excellent introduction to the politics of the region for the general reader.
Keywords: "International politics, Political science, Guneratne, Ar"